The use of embodied self-rotation for visual and spatial perspective-taking - Surtees, Andrew D.; Apperly, Ian A.; Samson, Dana (Frontiers in Human Neuroscience, 2013)
Previous research has shown that calculating if something is to someone’s left or right involves a simulative process recruiting representations of our own body in imagining ourselves in the position of the other person (Kessler & Rutherford, 2010). We compared left and right judgements from another’s spatial position (spatial perspective judgements) to judgements of how a numeral appeared from another’s point of view (visual perspective judgements). Experiment 1 confirmed that these visual and spatial perspective judgements involved a process of rotation as they became more difficult with angular disparity between the self and other. There was evidence of some difference between the two, but both showed a linear pattern. Experiment 2 went a step further in showing that these judgements used embodied self rotations, as their difficulty was also dependent on the current position of the self within the world. This effect was significantly stronger in spatial perspective-taking, but was present in both cases. We conclude that embodied self-rotations, through which we actively imagine ourselves assuming someone else’s position in the world can subserve not only reasoning about where objects are in relation to someone else but also how the objects in their environment appear to them.